Role of weights in improving the efficiency of Kim and Warde's mixed randomized response model. Issue 4 (16th February 2016) - Singh, Housila P.; Tarray, Tanveer A.
ABSTARCT: In this paper we have suggested a class of unbiased estimators of π S, the proportion of respondents possessing a sensitive attribute A using mixed randomized response model. The variance of the proposed class of estimators has been obtained. In addition to Kim and Warde's (2005) estimator, several other acceptable estimators of π S have been identified from the proposed class for suitable weights. It has been shown that the newly identified estimators are more efficient than the Kim and Warde's (2005) estimator. Numerical illustrations and graphs are also given in support of the present study.